A Longer Duration of Intravenous Antibiotic Treatment for Patients with Early Periprosthetic Joint Infections Is Not Associated with a Lower Failure Rate - Janneke Meijer; Alex Soriano; Wierd Zijlstra; Bas ten Have; Saad Tarabichi; Paul Jutte; Javad Parvizi; Marjan Wouthuyzen-Bakker (Antibiotics)
Background: In recent years, many studies have demonstrated the efficacy of an early switch to oral antibiotics after surgical treatment in orthopedic-related infections. However, large analyses on periprosthetic joint infections (PJIs) are lacking. Material and Methods: We conducted a retrospective observational multicenter study in patients diagnosed with an early post-operative PJI, defined as one occurring <3 months after the index arthroplasty and treated with debridement, antibiotics, and implant retention (DAIR). Patients from Europe and the USA were included. We took advantage of the fact that an early oral antibiotic switch is routine practice in Europe as opposed to a long duration of intravenous (IV) antibiotic treatment in the USA. Failure was defined as the clinical need for (i) a second unintended DAIR procedure, (ii) implant removal, (iii) suppressive antibiotic treatment, or (iii) PJI-related death, all within one year after DAIR. Results: A total of 668 patients were included. A total of 277 received IV antibiotics for <14 days, 232 between 14 and 27 days, and 159 for >27 days. The overall 1-year failure rate within the 3 groups was 41.5%, 44.4%, and 42.1%, respectively (p = 0.80). This observation remained when excluding patients who failed during IV therapy. A longer duration of IV therapy seemed beneficial for those patients with a high pre-operative C-reactive protein level and lack of modular component exchange. Conclusions: In early post-operative PJIs, a longer duration of IV therapy is not associated with a lower failure rate but may be continued until a sufficient bacterial load reduction has been achieved.